General geology - Foster, Robert J. (Robert John) (Columbus : Merrill Publishing Company, 1973)
This edition was made at the request of many students who wanted more information of how geology directly affects their lives.
Part One. Composition of the crust - minerals and rocks -- Part Two. The external processes - erosion -- Part Three. Internal processes - structural geology -- Part Four. Earth history.
Keywords: GEOLOGY